Reliability of medical students' vaccination histories for immunisable diseases - Gottschalk René; Allwinn Regina; Wicker Sabine; Rabenau Holger F (BMC, 2008)
Abstract Background Medical students come into contact with infectious diseases early on their career. Immunity against vaccine-preventable diseases is therefore vital for both medical students and the patients with whom they come into contact. Methods The purpose of this study was to compare the medical history and serological status of selected vaccine-preventable diseases of medical students in Germany. Results The overall correlation between self-reported medical history statements and serological findings among the 150 students studied was 86.7 %, 66.7 %, 78 % and 93.3 % for measles, mumps, rubella and varicella, conditional on sufficient immunity being achieved after one vaccination. Although 81.2 % of the students' medical history data correlated with serological findings, significant gaps in immunity were found. Conclusion Our findings indicate that medical history alone is not a reliable screening tool for immunity against the vaccine-preventable diseases studied.